THE EFFECT OF LENDERS, QUICK RATIO, AND NPM ON PROFIT MANAGEMENT IN THE FOOD AND BEVERAGE SUB-SECTOR 2021-2024 - Syukur Niaman Telaumbanua; Nurul Izzah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the effect of Long Term Debt to Equity Ratio (LTDER), Quick Ratio (QR), and Net Profit Margin (NPM) on earnings management in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. Earnings management also fluctuated and tended to show negative values. The results of partial hypothesis testing (t-test) indicate that LTDER, Quick Ratio, and NPM have no significant effect on earnings management. The simultaneous test (F-test) also shows that the three independent variables together have no significant effect on earnings management. The coefficient of determination (R²) is 5.6%, which means that only a small portion of earnings management variation can be explained by LTDER, Quick Ratio, and NPM, while the remaining is influenced by other factors outside this study. Thus, it can be concluded that LTDER, Quick Ratio, and NPM are not the main determinants of earnings management practices in food and beverage sub-sector companies listed on the IDX for the period 2021–2024.